Study Guide for Technical Analysis of the Financial Markets : A Comprehensive Guide to Trading Methods and Applications - Murphy, John J (New York New York Institute of Finance, 1999)
This study guide accompanies "Technical Analysis of the Financial Markets", describing all the concepts in the book and their appplications. It shows how to apply the principal of technical analysis to all markets.
Include Illustrations and Index
Keywords: Commodity exchanges